Transitivity Analysis in Short Story “The Last Leaf” By O. Henry - Hanifa, Suci; Ardi, Havid (English Language and Literature, 2023)
The purpose of this research to find the process type found in the short story titled The Last Leaf by O. Henry. The method used in this research is qualitative descriptive, while the data were taken from the short story. In Systematic Functional Linguistics, it is the approach used to analyze the text and context. Where SFL itself is the study of function language divided the function into three are Textual Function, Interpersonal Function, and Ideational Function. Ideational Function is express the idea and experience, that experience is language illustrated how people is view of the world as consisting of “ going-on or what happen” (verb) included things (as noun) and attributive (as adjective) and other such as place, manner and time (as adverb) or we call as transitivity aspect. The result of study, the dominant process used in the source text and target text that are 120 process for Material Process, 35 process for Mental process, 49 process for Relational process for source text, and 111 process for Material Process, 44 process for Mental process, 30 process for Relational process in target text. Therefore, Material, Mental, Relational is the dominant used type process in the some text especially in narrative text, as (Gerot and Wignell 1995) said some typical Processes are found in the text type such as Mental, Material and Relational Processes.